Phenomenological Analysis of Communication Patterns of Prospective Brides in Determining the Quantity of Dowry Based on Community Problems - Putri Munawwarah; Kurrniawati, Dewi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This research discusses the phenomenological analysis of communication patterns of prospective brides and grooms in determining the quantity of dowry based on the problems of a case study community in the Acehnese tribe. The aim of this research is to analyze the determination of the quantity of dowry from prospective brides and the determination of the quantity of dowry based on problems that exist in society such as committing immoral acts in order to carry out forced marriages without dowry with the habit of taking the law into their own hands. This research focuses on the prospective bride, prospective groom and the parties involved. This research is a literature study method research by collecting library data, reading, taking notes and processing research materials. The results obtained are that to eliminate community problems, good communication patterns need to be implemented with prospective brides and grooms, families and traditional leaders.